2017
DOI: 10.1186/s40035-017-0097-1
|View full text |Cite
|
Sign up to set email alerts
|

Nicorandil potentiates sodium butyrate induced preconditioning of neurons and enhances their survival upon subsequent treatment with H2O2

Abstract: BackgroundExtensive loss of donor neural stem cell (NSCs) due to ischemic stress and low rate of differentiation at the site of cell graft are two of the major issues that hamper optimal outcome in NSCs transplantation studies. Given that histone deacetylases (HDACs) modulate various cellular processes by deacetylating histones and non-histone proteins, we hypothesized that combined treatment with small molecules, sodium butyrate (NaB; a known HDAC inhibitor) and nicorandil, will enhance the rate neuronal diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…24 For combined treatment, Nico was added to the culture media with concentrations of 12 µM on day 3 after start of NaB treatment as described earlier. 24 LY294002 at the final concentration of 10 µM for 48 hours used as a phosphatidylinositol-3 kinase (PI3K) inhibitor 25 and also AR03 (cat #2136; Axon Medchem, Groningen, The Netherlands) at the concentration of 1 µM as specific APE1 inhibitor. 26 These inhibitory small molecules were used to loss of function and confirm their specific roles in each cascade.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…24 For combined treatment, Nico was added to the culture media with concentrations of 12 µM on day 3 after start of NaB treatment as described earlier. 24 LY294002 at the final concentration of 10 µM for 48 hours used as a phosphatidylinositol-3 kinase (PI3K) inhibitor 25 and also AR03 (cat #2136; Axon Medchem, Groningen, The Netherlands) at the concentration of 1 µM as specific APE1 inhibitor. 26 These inhibitory small molecules were used to loss of function and confirm their specific roles in each cascade.…”
Section: Methodsmentioning
confidence: 99%
“…24 For combined treatment, Nico was added to the culture media with concentrations of 12 µM on day 3 after start of NaB treatment as described earlier. 24 For combined treatment, Nico was added to the culture media with concentrations of 12 µM on day 3 after start of NaB treatment as described earlier.…”
Section: Small Molecules Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, 5 × 10 5 cells were collected and incubated with Annexin V-FITC for 5 min at room temperature in the dark. Afterward, the cells were detected by flow cytometry using Flow Cytometer laser 488 nm (Becton Dickinson, NJ) and analyzed with FlowJo™ Software [31].…”
Section: Annexin V Stainingmentioning
confidence: 99%
“…Hence, it is imperative to reinforce the donor cell to withstands the rigors of the microenvironment of the infarcted site by optimizing cell engraftment and this without increasing complications [82]. Authors had shown in stroke [83] and in myocardial infarction [80], that priming cells prior transplantation with cytokines to a state of "readiness" by stimulating their survival pathways will fortify cell engraftment leading to enhance survival and to overcome numbers of problems occurring during the post engraftment period.…”
Section: Different Cell Doses Have Been Used In the Includedmentioning
confidence: 99%